2001
DOI: 10.1002/1522-2683(200101)22:1<134::aid-elps134>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of doxorubicin, daunorubicin, and idarubicin by capillary electrophoresis with laser-induced fluorescence detection

Abstract: The separation and simultaneous determination of doxorubicin, daunorubicin and idarubicin was investigated using capillary electrophoresis with laser-induced fluorescence detection. Because the three anthracycline antibiotics were similar in structure and mass, careful manipulation of the electroosmotic flow and electrophoretic mobilities was required. A buffer consisting of 100 mM borate, adjusted to pH 9.5, containing 30% acetonitrile was found to provide a very efficient and stable electrophoretic system fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 4 publications
2
24
0
Order By: Relevance
“…Liquid‐liquid extraction (LLE) is the classical approach for anthracycline extraction from urine11–15 using chloroform as the solvent of choice but this technique is time consuming and requires large volumes of an expensive and toxic solvent. A substantial improvement for biological matrices sample preparation techniques resulted from the development of SPE, using bonded silica sorbents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid‐liquid extraction (LLE) is the classical approach for anthracycline extraction from urine11–15 using chloroform as the solvent of choice but this technique is time consuming and requires large volumes of an expensive and toxic solvent. A substantial improvement for biological matrices sample preparation techniques resulted from the development of SPE, using bonded silica sorbents.…”
Section: Methodsmentioning
confidence: 99%
“…The development of an analytical method for quantifying these four analytes in the urine of people who are occupationally exposed to these antibiotics is described in this paper. A few high‐performance liquid chromatography methods with visible spectrophotometry (HPLC‐UV)4–9 have been reported for the determination of single anthracyclines, and many HPLC assays using fluorescence detection (HPLC‐FL) have recently been published 10–21. It should be noted that trace analysis at sub‐ppb levels can become feasible only if an improved detection system, such as fluorescence or mass detection (MS), is used.…”
mentioning
confidence: 99%
“…However, to our best knowledge, nobody has ever used CE for analyzing DOX release from conjugates with fullerene. Acetonitrile (ACN) in the DOX separation by CE has been used by many authors before [29,53]. Pérez-Ruiz et al [53] observed that the addition of ACN to the borate buffer considerably improved the separation and caused only a moderate increase in analyte migration time.…”
Section: Capillary Electrophoresis Of Dox and Fullerene-dox Complexesmentioning
confidence: 99%
“…Acetonitrile (ACN) in the DOX separation by CE has been used by many authors before [29,53]. Pérez-Ruiz et al [53] observed that the addition of ACN to the borate buffer considerably improved the separation and caused only a moderate increase in analyte migration time. In our study, it was observed that the presence of ACN in the sample slightly improved LIF detection during the CE analysis (CE-LIF).…”
Section: Capillary Electrophoresis Of Dox and Fullerene-dox Complexesmentioning
confidence: 99%
“…Some methods are available to tackle this issue such as liquid-liquid extraction (LLE), liquidsolid extraction (LSE) and solid-phase extraction (SPE). Pérez-Ruiz et al (2001) mixed acetonitrile (50 μL) with blood serum (50 μL) and vortexed. The mixture was centrifuged and the supernatant collected, which was diluted with deionized water and used for CE analyses.…”
Section: Sample Preparationsmentioning
confidence: 99%